Interactive method for cumulative analysis of software formal models behavior - Kolchin, A. (Проблеми програмування, 2018)
The aim of the proposed method is to simplify and improve the process of models debugging and to increase efficiency of model-based test cases generation. Unlike existing methods of models behavior analysis, which produce as a result only one, usually first-found, path per specified property (which is an evidence of test goal reachability or explanation of some inconsistency during debugging process), the proposed method generates a projection of all satisfiable paths, which provokes exposure of undesired behavior. For test cases generation, the feature plays a role of interactive path constructor, which prompts all satisfiable behavior alternatives, so user can find a desired path by iteratively specifying points-of-interest. Appropriate novel algorithm for efficient searching is presented.